The Effect of Thesis Writing on Paraphrasing Ability of the EFL Alumni of the University of Mataram Lombok - Arifuddin Arifuddin (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2021)
Until recently, no study focused on analyzing the effect thesis writing program on paraphrasing ability of the alumni. Generally, some studies focused on the reversed direction, that is, the effect of paraphrasing ability on thesis writing. This is the novelty of the present study. The present study aimed at testing the effect of thesis writing program at the end of the EFL study on paraphrasing ability of the alumni an EFL education, identifying the types of paraphrasing, and exploring weaknesses in paraphrasing and causes of not paraphrasing. This evaluative ex-post facto research employed Mixed-methods. The participants were 68 alumni of the University of Mataram Indonesia, those who undertook thesis writing program during their study in EFL education and the others who did not write undergraduate thesis. They were selected purposively from 37 schools in West Nusa Tenggara province. Data were collected with writing tasks, questionnaire, interview, and recording. The data were analyzed quantitatively and qualitatively. It shows: 1) The level of the alumni’s paraphrasing ability is ‘medium’; 2) Thesis writing program affects paraphrasing ability of the EFL alumni; 3) Synonym and Change of Word Orders are the dominant techniques; 4) The teachers’ weaknesses involve lack of vocabulary, limited conversions, deviation from the authentic ideas, summarizing, and unclear paraphrasing, 5) The causes of not paraphrasing include limited knowledge of paraphrasing and grammatical understanding. It is suggested that teacher education institutions implement curriculums that support teachers’ writing skills. In turn, plagiarism could be minimized which leads to the production of teachers’ quality academic writing.